Conceptualización de una unidad de inteligencia de negocios en una empresa de tercerización de servicios : Caso IQ Outsourcing S.A.S. (2015)
"There are processes in different private and public entities that involve a great effort and investment in information gathering, implementation of solutions, maintenance and management of operational resources, which when compared to the mission of these entities are not very related to your business. On the other hand, the time required to carry out an initiative depends on these processes insofar as they are given attention and allocation of resources. Some of these processes are known, in the financial and services sector, as back office (business support activities, which are not visible to the client or end user) transactional responsible for carrying out tasks of document management, call center (telephone call management center), information analysis among other more specialized ones; that ultimately do not represent profits but are understood as expenses and are not taken into account as part of the solutions or market strategies that they offer their clients. To help these entities, there are external service companies that assume to some extent these tasks, from the transfer of activities to another company that is responsible for carrying out the execution of the same, to alliances with companies that are not only limited to comply with service agreements, but advise and help evolve entities towards new and better ways to provide their services ... "- Extract of the document